Impact of premature rupture of membranes on clinical outcomes of extremely premature infants: A propensity score matching study - Cao, Jing-Ke; Liu, Chang-Geng; Wang, Dan; Li, Qiu-Ping (Frontiers in Pediatrics, 2023)
Background: Premature rupture of membranes (PROM) is a common cause of extremely premature infants (EPIs) and also leads to adverse preterm complications. However, the effect of PROM on EPIs remains contradictory. This study used propensity score matching (PSM) to adjust the baseline characteristics to explore the impact of PROM on clinical outcomes of extremely premature infants (EPIs). Methods Medical data of 470 EPIs at gestational age < 28weeks who received prenatal examination in our hospital between January 1, 2015 and December 31, 2020 were analyzed retrospectively. According to the presence or absence of PROM, they were divided into a PROM group and a non-PROM group. Ten covariates including birth weight, male sex, artificial conception, cesarean delivery, 5-min Apgar score ≤ 7, oligohydramnios, gestational hypertension, preeclampsia, antenatal steroid use, and complete steroid treatment were matched 1:1 by PSM. The major complication occurrence and mortality during hospitalization were compared between the two groups by t-test, nonparametric test or x^2test. Results Among the 470 infants enrolled, 157 (33.4%) were in PROM group and 313 in no-PROM group. After matching the ten confounding factors,276 cases were successfully enrolled. The incidence of early pulmonary hypertension (EPH) and severe retinopathy of prematurity (ROP) in PROM group were higher than those in no-PROM group [44.2% (61/138) vs. 29.0% (40/138); 34.8% (48/138) vs. 21.7% (30/138), x^2=6.886 and 5.790, both P <0.05].However, there was no significant difference in the in-hospital mortality and the incidence of other major complications between the two groups(all p >0.05). Conclusions PROM increased the incidence of EPH and severe ROP in EPI, but had no significant impact on in-hospital mortality, length of hospital stay, and the incidence of other complications.